Recent management of urinary stone disease in a pediatric population - Aydogdu, Ozgu (Baishideng Publishing Group Co., Limited, 2014)
The incidence of stone disease has been increasing and the risk of recurrent stone formation is high in a pediatric population. It is crucial to use the most effective method with the primary goal of complete stone removal to prevent recurrence from residual fragments. While extracorporeal shock wave lithotripsy (ESWL) is still considered first line therapy in many clinics for urinary tract stones in children, endoscopic techniques are widely preferred due to miniaturization of instruments and evolution of surgical techniques. The standard procedures to treat urinary stone disease in children are the same as those used in an adult population. These include ESWL, ureterorenoscopy, percutaneous nephrolithotomy (standard PCNL or mini-perc), laparoscopic and open surgery. ESWL is currently the procedure of choice for treating most upper urinary tract calculi in a pediatric population. In recent years, endourological management of pediatric urinary stone disease is preferred in many centers with increasing experience in endourological techniques and decreasing sizes of surgical equipment. The management of pediatric stone disease has evolved with improvements in the technique and a decrease in the size of surgical instruments. Recently, endoscopic methods have been safely and effectively used in children with minor complications. In this review, we aim to summarize the recent management of urolithiasis in children.